(untitled) - OCTAVIANY, BUNGA (RETAIN : Journal of Research in English Language Teaching, 2013)
This study is conducted to find out the teacher’s reasons for using dialogue reading in teaching speaking, to describe the implementation of dialogue reading to the tenth graders, and to describe how successful the teaching is to make them speak through non participant observation and teacher interview. This study used descriptive qualitative without any statistical calculation. The result of this study showed that the teacher used dialogue reading in class to make them easier to speak because she knew that they always interact with people in their daily life with dialogue. She wanted them to think that speak in English is not that hard as they thought. She wanted to increase her students’ confidence since they came from different cities and villages in Indonesia. The implementation of dialogue reading was held in two meetings which consists of three steps: beginning activity, main activity and last activity. The implementation of teaching speaking using dialogue reading was successful enough according to the teacher to make them speak. The students were able pronounce the words well, their intonation got better and they became more confident in speaking English. Keywords: Teacher’s reasons, implementation, Dialogue-Reading, successful teaching. Abstrak Penelitian ini bertujuan untuk mengetahui alasan guru dalam menggunakan dialogue reading untuk mengajar bebicara, untuk mendeskripsikan penerapan dialogue reading pada siswa kelas sepuluh, dan seberapa sukses dialogue reading mambuat siswa berbicara menurut guru. Penelitian ini menggunakan penelitian deskriptif qualitative tanpa ada perhitungan statistik. Hasil penelitian ini menunjukkan bahwa guru menggunakan dialogue reading di kelas supaya membuat siswa berbicara dengan mudah karna guru mengetahui bahwa mereka selalu berinteraksi dengan orang di dalan kehidupan mereka sehari-hari menggunakan dialogue. Guru ingin membuat mereka berpendapat bahwa berbicara dalam bahasa inggris tidak susah seperti yang mereka fikirkan. Guru pun ingin menambahkan rasa kepercayaan diri mereka karna mereka datang dari kota dan desa yang berbeda di Indonesia. Penerapan dialogue reading dilaksanakan dalam dua pertemuan yang mana terdiri dari tiga langkah: awal, inti dan akhir kegiatan. Penerapan dialogue reading sukses diterapkan, siswa dapat mengungkapkan kata dalam bahasa Inggris dengan benar, intonasi mereka menjadi lebih baik dan mereka menjadi lebih percaya diri dalam berbicara bahasa Inggis. Kata Kunci: Alasan guru, penerapan, Dialogue-Reading, pengajaran yang sukses.